A bibliometric analysis of climate engineering research. (30th May 2013) - Belter, Christopher W.; Seidel, Dian J.
Abstract : The past five years have seen a dramatic increase in the number of media and scientific publications on the topic of climate engineering, or geoengineering, and some scientists are increasingly calling for more research on climate engineering as a possible supplement to climate change mitigation and adaptation strategies. In this context, understanding the current state of climate engineering research can help inform policy discussions and guide future research directions. Bibliometric analysis—the quantitative analysis of publications—is particularly applicable to fields with large bodies of literature that are difficult to summarize by traditional review methods. The multidisciplinary nature of the published literature on climate engineering makes it an ideal candidate for bibliometric analysis. Publications on climate engineering are found to be relatively recent (more than half of all articles during 1988–2011 were published since 2008), include a higher than average percentage of nonresearch articles (30% compared with 8–15% in related scientific disciplines), and be predominately produced by countries located in the Northern Hemisphere and speaking English. The majority of this literature focuses on land‐based methods of carbon sequestration, ocean iron fertilization, and solar radiation management and is produced with little collaboration among research groups. This study provides a summary of existing publications on climate engineering, a perspective on the scientific underpinnings of the global dialogue on climate engineering, and a baseline for quantitatively monitoring the development of climate engineering research in the future. WIREs Clim Change 2013, 4:417–427. doi: 10.1002/wcc.229 This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives Social Status of Climate Change Knowledge > Knowledge and Practice